1981
DOI: 10.1115/1.3230798
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Premixed Combustion Flame Stabilizer Geometry on Flame Stability and Emissions

Abstract: Premixed combustion systems for gas turbines offer the possibility of low-pollution, high-combustion efficiency and good temperature distribution. They form a basis by which other well-mixed combustion systems may be assessed. The ultimate objective of this work is the development of nonpremixed rapid mixing combustion systems. Different geometries of baffle flame stabilizers are tested to study the influence of recirculation zone size and number of recirculation zones on flame stability, combustion efficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
1

Year Published

1983
1983
1998
1998

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 0 publications
2
29
1
Order By: Relevance
“…The two flame stabilisers were tested with premixed propane and air at the 0.03 Mach number condition. This was achieved, as in previous work (1,5), by injecting propane, through twenty holes in an 'X injector, 1.5 m upstream of the stabiliser. Fig.…”
Section: Premixed Combustionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two flame stabilisers were tested with premixed propane and air at the 0.03 Mach number condition. This was achieved, as in previous work (1,5), by injecting propane, through twenty holes in an 'X injector, 1.5 m upstream of the stabiliser. Fig.…”
Section: Premixed Combustionmentioning
confidence: 99%
“…This indicates that the stabiliser aerodynamics are good. Previous work has shown that premixed combustion with large recirculation zone systems such as baffles (1) or swirlers (6) result in a high combustion inefficiency and hence an inadequate basis for the design of weak primary zone systems.…”
Section: Premixed Combustionmentioning
confidence: 99%
“…The 76 mm diameter combustion test facility has been described by Al-Dabbagh and Andrews (18). It consists of an air supply from a fan, venturi flow metering, electrical preheater, 1.5 m long 76 mm diameter approach pipe, flange mounted swirler with integral central fuel injector, 330 mm long 76 mm diameter combustor and an exhaust system with a flame observation window located a short distance from the combustor exit.…”
Section: Combustion Test Equipment and Conditionsmentioning
confidence: 99%
“…Although these have some advantages, Ahmad et al (5)(6)(7)(8)(9) have shown that the NOx emissions and combustion efficiency of weak mixtures is not as good as in the present jet shear layer designs. The authors have extensively investigated various designs of jet shear layer fuelled systems for low emissions wide stability combustor primary zones (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). This work has concentrated on investigating factors that influence mixing, especially the number of air and fuel injection points (13) and the influence of pressure loss (12,14,15,19).…”
Section: Introductionmentioning
confidence: 99%
“…In the present work the -Jet Mix" design of interacting radial and axial jets was used (10,11,(16)(17)(18)(19)(20). This has been shown to have a good premixed performance (10) with a capability for direct fuel injection with the radial air that extends the stability whilst retaining low NOx emissions (11,(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%